The influence of the colors on the Creative Process in Dance - Souza, Mariana Cristina Tavares da Silva (2017)
To find other ways to expand the creative work in dance, this study looked to explore the creative process through the sensations and the emotions evoked by the colors. This research counted on the participation of ten students from the group of studies in dance and somatic education from the Federal University of Viçosa. Four workshops were made to assess the relevance between the colors and the creative process. The analyse were treated qualitatively. The results of this study showed that the application of the colors made it possible to find new ways to create a work more sensitive, expressive and perceptive of the emotions and the sensations towards the creation of the movement in dance.